(untitled) (Al-Academy, 2024)
The act of building intellectual and cultural knowledge and concepts requires a dramatic, cognitive, and aesthetic formation to generate interpretive dimensions to form an objective and aesthetic distance for the viewer that takes space to polarize the foundations and scope of social issues and devise their social treatments according to the reading of difference and heterogeneity produced by the sociological imagination of the play righter. Naturally, feminist theater has particularity in recording social issues, and from here emerges the problem of the current research: What is the sociological imagination of the Iraqi feminist writer?, the research aims to identifying the sociological imagination in feminist theatrical text, the research was limited to texts by Iraqi women writers for the period from (2018-2022), they are five texts. The test of two plays of ( Ayoob) and ( Istytan) were subjected to analysis.The research included two sections, the first of which specialized in studying the sociological imagination conceptually. The second section was concerned with studying the sociological imagination in feminist theater texts internationally and Iraqi.One of the most important results of the research:- 1. The feminist writer invested sociological imagination in her theatrical texts as a creative writing technique through which she wanted to explore social and political issues in a different and contradictory manner to the reality to open the horizon of critical thinking and interpretation for the viewer.2. It used the sociological imagination as a tool to create characters that, despite their realism, are complicated by their psychological illnesses left behind by societies and their autocratic institutions, which made them a depressed spirit framed by policies of fear, alienation, deprivation, and persecution.